The effect of tafamidis on the QTc interval in healthy subjects. (June 2015) - Klamerus, Karen J.; Watsky, Eric; Moller, Robert; Wang, Ronnie; Riley, Steve
<x xml:space="preserve">Abstract</x> Aims The transthyretin (TTR) stabilizer, tafamidis, has demonstrated efficacy and safety in the treatment of TTR familial amyloid polyneuropathy (20 mg day−1). Tafamidis use in TTR cardiomyopathy led to the study of the potential effect of tafamidis on the QTc interval in healthy subjects. Methods This randomized, three treatment, three period, six sequence crossover study with placebo, a positive control (moxifloxacin 400 mg) and tafamidis (400 mg, to achieve a supra‐therapeutic Cmax of ~20 µg ml−1) was conducted in healthy volunteers at three clinical research units. Oral dosing in each of the three treatment periods was separated by a washout period of ≥ 14 days. Serial triplicate 12‐lead electrocardiograms were performed. QTc intervals were derived using the Fridericia correction method. Safety and tolerability were assessed by physical examination, vital signs measurement, laboratory analyses and monitoring of adverse events (AEs). Results A total of 42 subjects completed the study. The upper limit of the two‐sided 90% confidence intervals (CIs) for the difference in baseline‐adjusted QTcF between tafamidis 400 mg and placebo was <10 ms (non‐inferiority criterion) for all time points. The lower limit of the two‐sided 90% CI between moxifloxacin 400 mg and placebo exceeded 5 ms at the pre‐specified moxifloxacin tmax of 3 h post‐dose, confirming assay sensitivity. Cmax and AUC(0, 24 h) for tafamidis were 20.36 µg ml−1 and 305.4 µg ml−1 h, respectively. There were no serious/severe AEs or treatment discontinuations due to AEs. Conclusions This thorough QTc study suggests that a supra‐therapeutic single 400 mg oral dose of tafamidis does not prolong the QTc interval and is well‐tolerated in healthy volunteers.